COVID-19 Pandemic and Mental Health of Vulnerable Two Groups: Developmental Trauma of the Child-Adolescents and Work Disaster of Health Care Workers - Nam, Seok Hyun (Chonnam Med J, 2021)
COVID-19 has spread worldwide. People are struggling to adjust to a new normal, but changes in their daily routines are also causing stress. A person may feel depressed, uneasy, or suicidal and may complain of symptoms such as panic attacks, post-traumatic stress disease (PTSD), psychosis, obsessive–compulsive disorder, or paranoia when personal resilience cannot effectively process the stress. Children, adolescents, and health care workers are especially psychologically vulnerable groups in the pandemic calamity situation; therefore, a long-term intervention plan is necessary for them. When intervening with children and adolescents, it should be considered that each individual has different ways of expressing stress according to the developmental level of cognition, language, and emotion, and taking into account these developmental levels, it is necessary to help them achieve developmental tasks appropriate for their age. Health care workers feel psychological pain from problems such as the risk of becoming infected, the risk of passing the virus to their families, overwork, isolation, and stigma. Therefore, it is necessary to help them recover themselves by supplying personal protective equipment and providing the most basic resources necessary for adequate rest, work-life balance, and childcare.